Applicability and Effectiveness of Closed Reduction of Nasal Fractures under Local Anesthesia - Vilela, Fernando; Granjeiro, Ronaldo; Maurício, Carlos, Júnior; Andrade, Patrícia (International Archives of Otorhinolaryngology, 2014)
Introduction A significant portion of patients treated in emergency departments have nasal fracture. It is important that the otolaryngologist know how to treat such damage.Objectives To evaluate the effectiveness of nasal fracture reduction under local anesthesia and tolerance to the procedure.Methods Twenty-four patients treated in the emergency department with closed reduction under local anesthesia were prospectively followed. Epidemiologic information and data regarding pain and complications during the management were noted. The degree of satisfaction was researched by visual analog scale.Results The majority of patients were male (75%), and the most common cause of injury was motor vehicle accident. We found a significant association between time to reduction and referred pain during the procedure. In patients in whom the procedure was delayed (over 3 days), there was less pain, and those who bled during the procedure had a shorter average time to reduction than the group of patients who did not bleed. Most patients were very satisfied, with more than 95% of these willing to undergo the same process again, if necessary.Conclusions The closed approach in the clinic under local anesthesia was effective and safe in restoration of the nose.
Keywords: traumatology; nasal bone; nose deformities; acquired